Considerações gerais sobre os resíduos eletrônicos - Norte, Ana Carolina Cunha [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
As new technologies improve, people’s lives gain in comfort and accessibility. However, along with these technologies comes a growth in “soon to fall into disuse” product consume, either because they have reached the end of their life cycle, or because they were substituted by newer and more advanced models. These electronic wastes are still with no certain destination, and could be donated to welfare companies, but the majority is thrown in wide open dumping grounds or landfills, where they can contaminate water and soil with their toxic components. This work seeks to evaluate the e-waste concept, their impacts in the environment and human life, as well as the current national and international e-waste management and destination, finally reflecting on international decisions that would be appropriate for the Brazilian system.

O avanço das novas tecnologias traz comodidade e melhorias à vida das pessoas. Mas junto a essa tecnologia cresce o consumismo e multiplicam-se produtos que logo caem em desuso, ora por terem atingido o fim do seu ciclo de vida, ora porque foram substituídos por modelos mais novos e mais avançados. Os eletrônicos pós-consumo seguem, então, sem rumo certo, podendo ser doados para entidades de pessoas carentes como forma de inclusão social, mas muitas vezes são jogados sem cuidados em lixões a céu aberto e aterros, de onde passam a contaminar solo e água com seus componentes tóxicos. O presente trabalho busca estudar o conceito de resíduos de eletrônicos, seus impactos ao meio ambiente e à vida humana, assim como o atual quadro de gerenciamento e disposição final desses resíduos nacional e internacionalmente, por fim trazendo ponderações de decisões internacionais que se adequariam ao cenário brasileiro.
Keywords: Resíduos; Waste